2018
DOI: 10.3126/ajms.v9i5.19910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cimetidine on cyclophosphamide-induced liver toxicity in albino rats

Abstract: Background: The clinical use of cyclophosphamide (CP) has been characterised by liver toxicity.Aims and Objectives: This research assessed the effect of cimetidine against CP-induced liver toxicity in a rat model.Material and Methods: Forty eight albino rats divided into 8 groups (A-H) of 6 rats per group gage were used for this study. Group A (control) was administered with water while groups B-D were administered with 5, 10, and 20 mg/kg/day of cimetidine intraperitoneally (ip) for 5 days respectively. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…Further studies confirm typical liver damage associated with CP administration [48][49][50]. Moreover, this was confirmed by other recent histopathological studies [47,[51][52][53], in which major CP induced histopathological alterations in liver tissue were periportal inflammation, inflammatory cells infiltration, hemorrhage, congestion of blood vessels, hepatocyte necrosis around the central veins, pyknosis of nuclei, cellular disintegration, and distortion.…”
Section: Discussionsupporting
confidence: 85%
“…Further studies confirm typical liver damage associated with CP administration [48][49][50]. Moreover, this was confirmed by other recent histopathological studies [47,[51][52][53], in which major CP induced histopathological alterations in liver tissue were periportal inflammation, inflammatory cells infiltration, hemorrhage, congestion of blood vessels, hepatocyte necrosis around the central veins, pyknosis of nuclei, cellular disintegration, and distortion.…”
Section: Discussionsupporting
confidence: 85%
“…Data from the present study showed that animals induced with toxicity using hydrogen peroxide showed elevated plasma AST activity. This finding corroborates previous studies that demonstrated rise in plasma AST and ALT activities, indicating hepatic damage [38,39]. Also, another study on the chemoprotective activity of aqueous leaf extract of Acalypha wilkesiana against cyclophosphamide-induced toxicity in rats [40].…”
Section: Effects Of Acalypha Godseffiana Aqueous Leaf Extract On Antioxidant Enzymessupporting
confidence: 92%
“…This study assessed the potential of DEXA to be repurposed as a hepatoprotective agent against CP-induced hepatotoxicity in albino rats. The alterations in the physiologic and metabolic functions of the liver accompanied by elevations in serum ALT, AST, ALP, LDH, GGT, CB and TB levels are basic features of hepatotoxicity caused by CP [24]. In this study, notable hepatotoxicity occurred in CP-treated rats marked by remarkable elevations in serum and liver levels of the aforementioned parameters.…”
Section: Discussionmentioning
confidence: 56%